Biofuels, Poverty, and Growth: A Computable General Equilibrium Analysis of Mozambique - Arndt, Channing; Benfica, Rui; Tarp, Finn; Thurlow, James; Uaiene, Rafael (2012)
This paper assesses the implications of large-scale investments in biofuels for growth and income distribution. We find that biofuels investment enhances growth and poverty reduction despite some displacement of food crops by biofuels. Overall, the biofuel investment trajectory analyzed increases Mozambique's annual economic growth by 0.6 percentage points and reduces the incidence of poverty by about 6 percentage points over a 12-year phase-in period. Benefits depend on production technology. An outgrower approach to producing biofuels is more pro-poor, due to the greater use of unskilled labor and accrual of land rents to smallholders, compared with the more capital-intensive plantation approach. Moreover, the benefits of outgrower schemes are enhanced if they result in technology spillovers to other crops. These results should not be taken as a green light for unrestrained biofuels development. Rather, they indicate that a carefully designed and managed biofuels policy holds the potential for substantial gains.